Mapping the research of travel live streaming: A bibliometric analysis using Vosviewer - Chen Yanhao; Hasrina Mustafa; Tan Poh Ling (Cogent Social Sciences)
As an emerging form of live streaming, travel live streaming is enjoyed by people worldwide. Existing studies on travel live streaming have failed to reflect the research and development in the field intuitively and systematically.This study is the first attempt to uses a bibliometric approach to review research on travel live streaming,A total of 930 studies published between 2015 and 2023 were extracted from the Web of Science and scientifically mapped using the VOSviewer software.The findings show that (a)The largest contributor to travel live streaming research is China, followed by the United States (b)The cluster analysis revealed that travel live streaming is now focusing on four areas: consumption, technology, platforms and teaching (c)The most influential authors and publications were identified.This study’s findings contribute to a better understanding of travel live streaming research,Promote the sustainability of relevant research.